Conservation Agriculture and Soil Organic Carbon: Principles, Processes, Practices and Policy Options - Francaviglia, Rosa; Almagro, María; Vicente-Vicente, José Luis (Soil systems, 2023)
Intensive agriculture causes land degradation and other environmental problems, such as pollution, soil erosion, fertility loss, biodiversity decline, and greenhouse gas (GHG) emissions, which exacerbate climate change. Sustainable agricultural practices, such as reduced tillage, growing cover crops, and implementing crop residue retention measures, have been proposed as cost-effective solutions that can address land degradation, food security, and climate change mitigation and adaptation by enhancing soil organic carbon (SOC) sequestration in soils and its associated co-benefits. In this regard, extensive research has demonstrated that conservation agriculture (CA) improves soil physical, chemical, and biological properties that are crucial for maintaining soil health and increasing agroecosystem resilience to global change. However, despite the research that has been undertaken to implement the three principles of CA (minimum mechanical soil disturbance, permanent soil organic cover with crop residues and/or cover crops, and crop diversification) worldwide, there are still many technical and socio-economic barriers that restrict their adoption. In this review, we gather current knowledge on the potential agronomic, environmental, and socio-economic benefits and drawbacks of implementing CA principles and present the current agro-environmental policy frameworks. Research needs are identified, and more stringent policy measures are urgently encouraged to achieve climate change mitigation targets.